MANAJEMEN KONFLIK SEBAGAI VARIABEL PEMODERASI HUBUNGAN ANTARA RELATIONSHIP CONFLICT DENGAN KREATIVITAS DAN KEPUASAN ANGGOTA TIM - Wibisono, Kunto (Benefit, 2005)
The basic aim of this research is to examine the relationship conflicts with teams creativityand team members satisfaction, also the conflict management behavior (contending, collaborating,and avoiding) which take place in 77 teams of 14 Event Organizer in Jogjakarta. In analyzingthe data, researcher used regression and hierarchical regression method. The result indicates there are relationships between conflicts with creativity and teammembersâ satisfaction. Conflicts do not have any negative effect to the creativity. This research findsthe conflictâs positive effect to the creativity, also with the conflict management although it is notmoderating the relationship between conflict and creativity likewise the membersâ satisfaction aboutthe team; collaborating conflict management has not a positive influence to the membersâ satisfactionabout the team. The reason is every member of the team wants way and solutions, which they allagree. The findings obtained in this research are expected could be used as a supplement reference forteams, especially the teams in Event Organizer to solve conflicts so the teams remain creative andon the other hand the members feel satisfy about their team.